The Digital Promotion of Japanese and Korean Movie in OTT Platform by Netflix - Daniel Susilo; Harliantara (PT FORMOSA CENDEKIA GLOBAL, 2023)
The emergence of internet streaming platforms has precipitated a fundamental transformation in the landscape of movie culture, transitioning it from conventional to digital formats. The advent of streaming platforms such as Netflix has significantly transformed the patterns of media consumption and the strategies employed for its promotion. Despite the novelty and appeal of this medium, particularly among younger generations, promotional strategies continue to rely on utilising content and streaming services to effectively engage customers. Content analysis is a research method employed to assess advertising strategies, with a specific emphasis on the utilisation of colour coding and cultural representation. The present study included a diverse range of advertising materials sourced from prominent streaming platforms across a span of time. This study focuses on the analysis of promotional colour schemes in order to identify recurring patterns or 'codes' associated with specific genres or topics. Furthermore, we analyse the utilisation of cultural elements in the promotional strategies employed by these platforms. These techniques have demonstrated a high level of effectiveness in effectively engaging their intended audience and enhancing awareness of the platform.